Youth mental health - Yong, Li Xuan (Nanyang Technological University, 2022)
In July 2021, the mental health of students in Singapore was thrust into the spotlight following the River Valley High School attack where a Secondary One student was allegedly struck to death with an axe by a Secondary Four student. The attack shook the nation. A week later, Education Minister Chan Chun Sing announced that the incidence of suicide among young people aged 10 to 19 rose in 2020 from 2019 as part of an overall increase in people here taking their own lives during the pandemic. Despite the prevalence of mental health issues, the stigma against this topic remains and youth struggle to seek counsel. Ms Ashley Poo Enhui, 21, is a Republic Polytechnic student who was diagnosed with depression and anxiety in November 2019. Through Fighting Demons, a photo essay about her mental health journey, I hope to pull back the curtain on depression and anxiety, and present readers with an unflinching look at how these mental disorders affect Ashley and her family.